ANALISIS PENGARUH RASIO LIKUIDITAS, ROFITABILITAS, SOLVABILITAS, AKTIFITAS DAN OPINI AUDIT GOING CONCERN TAHUN SEBELUMNYA TERHADAP OPINI AUDIT GOING CONCERN (Studi Empiris pada perusahaan real estate & property yang terdaftar di Bursa Efek Indonesia 2010-2013) - Febriana, Dorris; Sofianti, Septerina Prita Dania (Universitas Islam Negeri Sunan Kudus, 2016)
This researchaims to know the effect of liquidity, profitability, solvability, activities, and going concern audit opinion previous year to going concern audit opinion on the real estate and property companies on the Indonesian Stock Exchange 2010-2013. The samples in this research using purposive samplingand obtained a sample of 37 real estate companies and property in Indonesia Stock Exchange 2010-2013.Methods of analysis data using logistic regression. The results of this research indicate liquidity, profitability, solvability, activity does notinfluence the going concern audit opinion and going concern audit opinion previous year influence on the going concern audit opinion. The limitations of this research, financial ratios are less generalizable to other types of companies so that for future studies should use a financial proxy generalizable to various types of companies.